Contextual Learning By Using Batik Semarangan for Improving Students’ Learning Achievement - Hartanti, Rizka Silviana; Yulianto, Agus; Khumaedi, Khumaedi (Universitas Negeri Semarang, 2020)
This Research is aimed for knowing, (1) the implementation of contextual learning by using Batik Semarangan for physics material especially temperature and heat, (2) the improvement of students’ learning achievements after the application of contextual learning by using Batik Semarangan, and (3) the students’ responses after being given contextual learning by using Batik Semarangan. This research mix methods, namely quantitative and qualitative. This research was conducted in two classed at SMK Walisongo Semarang for student class X TKJ Telkom 1 as experimental class and X TKJ Telkom 2 as control class. The identification of local potential of Batik Semarangan was carried out by using interview and observation technique which were then analyzed qualitatively and the result was substituted to physics material, namely temperature and heat. Furthermore, learning achievements were assessed from sides of cognitive, affective and psychomotor. The result showed that contextual learning by using Batik Semarangan was effective for improving cognitive learning achievements as proved by experimental class having value of 0.79 which was higher than the control class of 0.57. In addition, the result showed that contextual learning by using Batik Semarangan was effective in improving effective learning achievements as proved by the experimental class average of 86.55 which was higher than the control class of 76.73. The result also showed that contextual learning by using Batik Semarangan was effective in improving psychomotor learning achievements as proved by the experiment class average score 33.3 higher than control class 25.4. The implementation of contextual learning by using Batik Semarangan got a positive responses by students because it made them easier to understand concepts, to be more skilled, and increased students’ interest in the learning process. Based on the result, it can be concluded that contextual learning with the use of Batik Semarangan can be applied to study temperature and heat material in classroom. Contextual learning with the use of Batik Semarangan can improve students’ learning achievement. Contextual learning with the use of Batik Semarangan got a good response by students.